MANAJEMEN INTEGRASI SISTEM INFORMASI PERPUSTAKAAN DILINGKUNGAN UNIVERSITAS INDONESIA DALAM MENUJU PERPUSTAKAAN DIGITAL - Anza, Fikri Akbarsyah; Fathmawati, Mayer (UI Scholars Hub, 2019)
This research discusses the integration of library information systems at the Universitas Indonesia (UI) with the UI Library to become a digital library. Currently, the integration that carried out is the transfer of physical collections into one place, transfer of human resources, and transfer of data. Even though integration already been done, problems related to that still appear, such as: related to governance, policy, and ITC. The focus of this research is to analyze the integration of library information systems in UI. The integration of library information systems is supported by the construction of software called the LONTAR (Library Automation and Digital Archive) system. In its implementation, not all faculty libraries agree with the integration. This is because there are several considerations such as difficult to access because not all faculties at UI are located in Depok so it takes longer to search the collection. In this research, the theory used is the theory of interoperability, especially related to the interoperability of organizations owned by Gottschalk & Saether. The results of this study is that the implementation of system integration is not supported by existing policies from UI so there is currently no clear SOP regarding the application of library information system integration in UI environment with the UI Library.